2011
DOI: 10.1037/a0024192
|View full text |Cite
|
Sign up to set email alerts
|

Consider it done! Plan making can eliminate the cognitive effects of unfulfilled goals.

Abstract: Unfulfilled goals persist in the mind, as asserted by ample theory and evidence (e.g., the Zeigarnik effect). The standard assumption has been that such cognitive activation persists until the goal is fulfilled. However, we predicted that contributing to goal pursuit through plan making could satisfy the various cognitive processes that usually promote goal pursuit. In several studies, we activated unfulfilled goals and demonstrated persistent goal activation over time. Unfinished goals caused intrusive though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 68 publications
7
118
0
1
Order By: Relevance
“…Also, it has been shown that desires can influence an individual's interpretation of ambiguous stimuli that assign the individual to a favored outcome (Balcetis & Dunning, 2006). Similarly, active goals can hinder performance on other tasks, which suggests attentional distraction from tasks that are unrelated to the goal (Masicampo & Baumeister, 2011a;Masicampo & Baumeister, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that desires can influence an individual's interpretation of ambiguous stimuli that assign the individual to a favored outcome (Balcetis & Dunning, 2006). Similarly, active goals can hinder performance on other tasks, which suggests attentional distraction from tasks that are unrelated to the goal (Masicampo & Baumeister, 2011a;Masicampo & Baumeister, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…This type of planning may include planning an adequate amount of time and even incorporating planned breaks to make goal achievement more likely (Gollwitzer, Gawrilow, & Oettingen, 2010). The mere act of planning for goal achievement also reduces the need for the exertion of further cognitive resources on unfulfilled goals (Masicampo & Baumeister, 2011). Consistent with this possibility, Benoit and colleagues (2011) find that prospection motivates individuals to make long-run beneficially decisions in the present as it shifts emphasis from the short-term, myopic, toward the long-term (Liu, Feng, Chen, & Li, Commuting as Planning Time 12 2013).…”
Section: The Benefits Of Goal-directed Prospection While Commutingmentioning
confidence: 51%
“…Goal-directed prospection can also serve to increase the likelihood employees will achieve their goals by serving as implementation intentions (Gollwitzer, 1999). Achieving more goals can reduce the amount of unfulfilled goals, which can additionally drain cognitive resources, thus imposing a strain on employees (Masicampo & Baumeister, 2011). By showing that engaging in specific thoughts can offset the negative effects of commuting -independently of trait self-control -we challenge the widespread notion that commuting is always negative, and provide a mechanism of how the negative effect can be reduced or even eliminated.…”
Section: Theoretical Contributionmentioning
confidence: 89%
“…Often people are intending to attain multiple goals at one time (Masicampo & Baumeister, 2011a, 2011b. In such a situation, these multiple goals are likely to compete for limited regulatory resources (Marien, Custers, Hassin, & Aarts, 2012;Shah & Kruglanski, 2002).…”
Section: Conservation Of Regulatory Resourcesmentioning
confidence: 99%